Increasing Halal Awareness among Micro and Small Enterprises (MSEs) through the Role of Halal Product Process Facilitators (P3H) in the Free Halal Certification Program (SEHATI) - Pajar Ramadan; Anisa Ilmia; Reza Fauzi Nazar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
The global halal industry continues to grow rapidly, positioning halal certification not only as a religious obligation but also as a key indicator of product quality, safety, and market competitiveness. As a country with the world’s largest Muslim population, Indonesia has considerable potential to strengthen its national halal ecosystem. However, the implementation of mandatory halal certification among Micro and Small Enterprises (MSEs) still faces several obstacles, particularly low halal awareness and limited understanding of certification requirements and procedures. To address these challenges, the Halal Product Assurance Agency (BPJPH) launched the Free Halal Certification Program (SEHATI) and involved Halal Product Process Assistants (P3H) to provide direct guidance to business actors. This study aims to (1) analyze the role of P3H in supporting the implementation of SEHATI, (2) examine the level of halal awareness among MSEs, and (3) identify supporting and inhibiting factors affecting halal awareness in Bandung Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving MSE owners and P3H assistants. The findings show that P3H plays an essential role as an educator, facilitator, and verifier, helping improve MSEs’ understanding of halal assurance and the steps required for certification. However, the effectiveness of this role is constrained by the limited number of active assistants, low halal literacy among business actors, and technical barriers in using the digital certification system. Overall, the study concludes that P3H significantly contributes to increasing halal awareness, yet further optimization through strengthened capacity, broader outreach, and better technological support remains necessary. Keywords: Halal Awareness, Halal Product Process Assistants (P3H), Micro and Small Enterprises (MSEs), SEHATI Program, Halal Certification.